EVALUATION OF THE PROFILE AND CONTENT OF CHLOROPHYLL PIGMENTS AND ACIDITY IN SELECTED COLD PRESSED OILS - Mińkowski, Karol; Bartosiak, Monika (Polish Journal of Natural Sciences, 2022)
The work evaluated the profile and content of chlorophyll pigments in cold pressed oils from rapeseed, flax, camelina, hemp, safflower, pumpkin, milk thistle, and from olive and avocado fruits, as well as the degree of hydrolysis of the oils examined. Content of chlorophylls a and b and their derivatives, being pheophytin a, pheophytin b, pyropheophytin a and pyropheophytin b were simultaneously determined in one sample, by modified and validated reversed phase HPLC method. The degree of hydrolysis of the oils was determined by their acid value. Market cold pressed oils have a very different content of chlorophyll pigments, regardless of whether they are from seeds or fruits. Considerable amounts were found in hemp oil (79.82 mg kg-1) and pumpkin oil (57.55 mg kg-1), and small quantity in flax oil (1.08 mg kg-1).The content of chlorophyll pigments in extra virgin olive oil was an intermediate level (15.44 mg kg-1). Chlorophyll derivatives dominate in the profile of chlorophyll pigments it is pheophytin a, pheophytin b, pyropheophytin a and pyropheophytin b. Extra virgin olive oil had the highest share of pheophytins, on average 82 %. A statistically significant correlation (r = 0.6509) was found between the percentage share of pheophytins in the total content of chlorophyll pigments and the acid value of extra virgin olive oil. It was noted that the percentage share of pyropheophytins in the total of pheophytins and pyropheophytins can be an indicator of the bioconversion of chlorophylls during storage of oils. There was a statistically significant negative correlation (r = –0.8836) between the percentage share of pyropheophytins in the total of pheophytins and pyropheophytins and the length of the period remaining until the expiry date of extra virgin olive oil.